2011
DOI: 10.1186/1472-6874-11-53
|View full text |Cite
|
Sign up to set email alerts
|

The facilitating factors and barriers encountered in the adoption of a humanized birth care approach in a highly specialized university affiliated hospital

Abstract: BackgroundConsidering the fact that a significant proportion of high-risk pregnancies are currently referred to tertiary level hospitals; and that a large proportion of low obstetric risk women still seek care in these hospitals, it is important to explore the factors that influence the childbirth experience in these hospitals, particularly, the concept of humanized birth care.The aim of this study was to explore the organizational and cultural factors, which act as barriers or facilitators in the provision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
1
39
0
4
Order By: Relevance
“…Attendance of unknown and unwanted persons during childbirth has been reported to be associated with dissatisfaction in women using childbirth services in Jordan [ 16 ]. The problem of maintaining privacy in the studied health facilities may be due to presence of a large number of health care professionals and student interns who might have interfered with women’s privacy, especially in the hospital; this may instill a lack of intimacy and affect the continuity of care women receive from health institutions [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attendance of unknown and unwanted persons during childbirth has been reported to be associated with dissatisfaction in women using childbirth services in Jordan [ 16 ]. The problem of maintaining privacy in the studied health facilities may be due to presence of a large number of health care professionals and student interns who might have interfered with women’s privacy, especially in the hospital; this may instill a lack of intimacy and affect the continuity of care women receive from health institutions [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Denying women this support is not only against evidence-based practice [ 20 ], but is also associated with dissatisfaction of women with childbirth services [ 21 ]. In addition, institutional rules and strategies that restrict the presence of a birth companion are reported to be a significant barrier to humanized birth care [ 7 , 18 ], exacerbating facility-based disrespect and abuse during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Another topic of debate concerns the model of care provided. Some authors argue in favour of more person-centred care with a focus on the needs expressed by the pregnant woman [ 8 , 9 ] However, such concepts are not always applied or interpreted in the same way [ 10 - 12 ], and what is actually implemented may therefore differ across healthcare providers. Nevertheless, in recent decades women, as end users of these services, have become key protagonists when it comes to deciding the kind of maternity care they want, and they have called for greater respect to be shown towards their wishes; in this context, user groups have sometimes put considerable pressure on health policymakers to ensure that the care offered is more respectful of the physiology of labour [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, more than half of the women in this study reported that this was disallowed. The mere presence of a birth companion can ensure respectful care (43) whereas restricting the presence of a birth companion is reported to be a signi cant barrier to humanized birth care (25,44,45). This suggests that health care providers know the way they behave in the absence of a companion is inappropriate and treat a client differently when a companion of the client is present (46).…”
Section: Discussionmentioning
confidence: 99%